SARS CoV-2 infection in health care workers first wave and second wave characteristics: a retrospective study from a tertiary care center - R., Shyamala; A. J., Lokesh (International Journal of Research in Medical Sciences, 2024)
Background: The Coronavirus disease (COVID-19) is a global pandemic that threatens lives and livelihoods. Healthcare workers (HCWs) fight the pandemic. The severe acute respiratory syndrome Coronavirus 2 (SARSCoV-2) pandemic has killed many HCWs worldwide. Methods: The study included all HCWs who tested positive for SARS-CoV-2. Data collection focused on demographics, job roles, disease presentation, and transmission risks, with statistical analysis performed using SPSS version 21.0 to evaluate infection trends and control efficacy. Results: The 2020 1st wave infected 93 HCWs and the 2021 second wave 145. The most affected were 25-35, with rates plummeting from 38-29%. Female infections rose 58-66%. Peak months were September to October 2020, April to May 2021. Nursing workers were 36% vulnerable, while technical staff infections jumped from 3% to 11%. COVID hospital staff had more infections in 1st wave, while non-COVID staff had more in second. Direct patient care threatened 36% in 1st wave and 42% in second. ICU infection rates fell from 10% to 6% with air filters. Hospital-acquired infections were 30%. Better personal protective equipment (PPE) management reduced risks from 10-3%. Conclusions: The study underscores the dynamic nature of the COVID-19 impact on HCWs, highlighting how effective vaccination and stringent infection controls can mitigate risks. Ongoing training in infection control, continuous adaptation of policies based on current data, and maintaining high vaccination rates are essential to protect HCWs in future waves or similar pandemics.